Unit Experimental Study on Impact Crushing Rock of the Microcoring PDC Bit. (3rd November 2019) - Yang, Yingxin; Song, Dongdong; Huang, Kuilin; Ren, Haitao; Zhou, Jian
Abstract : In light of the situation of sliced or powdery cuttings produced by conventional PDC bit, it is found that they are not convenient for geological logging and stratification. The unit crushing experiment which contains two breaking forms (static-pressure breaking and impact) is conducted on core columns of sandstone, limestone, and granite. This experimental study showed the following: The breaking work ratio of the three core column types is much less than that of the flat rock. The height of the core column has little effect on the bit penetration rate, while core column diameter has greater effect on the bit penetration rate. The experimental results further indicate that a core column has been generated in the central area of the drill bit, which is beneficial to the volume breaking of the rock and can improve the rock-breaking efficiency of the drill bit. The microcoring bit is suitable for raising speed in soft, medium, and hard formations and is helpful for geological logging.